Decomposition of Legal Constructions in Cross-Border E-Commerce Dispute Resolution from an International Civil Law Perspective - Yulia Anggraeni, Happy; Listiawati, Erna; Auriana Dewi, Anisya; Ragylia, R Tiara; Wahyu Utami, Febriyanti (Magister Hukum Universitas Semarang, 2025)
Digital transformation has driven a surge in cross-border transactions, but on the other hand, it has raised legal challenges related to jurisdiction, recognition of foreign judgments, and regulatory harmonization. The urgency of this research lies in the need for a legal framework that is fair, adaptive, and responsive to the complexities of international electronic commerce. This study aims to analyze the effectiveness of the application of International Civil Law (ICL) in the settlement of cross-border e-commerce disputes in the digital era. The method used is normative legal research based on a literature review, examining international regulations and practices of technology-based dispute resolution. The results of the study show that the harmonization of international regulations, the development of practical guidelines for e-commerce players, and clear regulations regarding the role of digital platforms are strategic steps to increase legal certainty and consumer confidence in cross-border transactions. This research offers novelty by emphasizing the integration of digital technology, including artificial intelligence and big data, in ADR-based dispute resolution mechanisms to strengthen effectiveness, legal certainty, and consumer confidence in the global arena.